Cosmoe's wiener getaway - Brallier, Max (Brallier, Max. Galactic hot dogs, 2020)
Over the course of one very strange night, Cosmoe went from being an adventure-seeking, thirteen-year-old Earthling orphan to a hot-dog-slinging space traveler. He has all the adventure he once craved and more aboard the Neon Wiener--part spaceship, part food truck--selling their trademark "Galactic Hot Dogs." Cosmoe and the rest of the crew journey to food competitions across the universe serving up the wildly popular wieners ... until they gain a troublesome stowaway. The half-evil, half-awesome Princess Dagger doesn't plan on going anywhere, and her presence on the ship means her all-evil mother is gunning for the Neon Wiener. Cosmoe rallies his friends to fight space jerks in all their many forms and vows to protect the princess. But can a group of hot dog enthusiasts face down an evil space queen?